Effective removal of chromium from contaminated water using horizontal subsurface flow constructed wetland with Napier grass (Pennisetum purpureum) - Taufik Taufikurahman; Lili Melani; Natasha Lumongga Hugo Sianturi; Ni Komang Devi Amrita Wirawan; Aisyah Fairuz Saifullah (Current Research on Bioscences and Biotechnology, 2023)
This study aims to explore the potential of using Napier grass (Pennisetum purpureum) as a low-cost alternative for treating wastewater contaminated with chromium (Cr) in the tannery industry. Traditional chemical treatment processes are costly, leading to many industries not committing to treatment. Phytoremediation, the use of plants to remove contaminants from the environment, could be a viable solution. The study conducted an experiment to test the tolerance and effectiveness of P. purpureum in treating wastewater containing Cr(VI) at concentrations of 20 ppm, 40 ppm, and tannery wastewater. The plant was grown in a constructed wetland pond using a batch system for 31 days. The results indicate that P. purpureum can survive and grow well in all treatments, showing tolerance to Cr. The plant's phytoremediation capacity was effective at 20 ppm of Cr(VI) as demonstrated by the chemical and physical characteristics of the medium (BOD, COD, pH, and TDS). The plant was able to remove a significant amount of total Cr and Cr(VI), with removal capacity ranging from 71.79% to 99.96%. The translocation factor (TF) for Cr in the roots was less than one, indicating that the plant has the potential to be used as a phytoremediator for Cr by accumulating it in its roots.